Development of Busy Book Media to Improve Elementary Second Grade Students’ Understanding of Pancasila Symbols - vania Gita; Etri Wahyuni; Hasmain Bungsu Ladiva; Yesi Anita (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the low understanding of second-grade elementary students on Pancasila symbols and values, as well as the limited use of engaging and interactive learning media. Therefore, a busy book learning media was developed to improve the learning process. The aim of this study was to determine the validity, practicality, and effectiveness of the developed media. The research used a Research and Development (R&D) method with the 4D model, consisting of define, design, develop, and disseminate stages. The subjects included material experts, language experts, media experts, second-grade teachers, and students from several elementary schools in Painan Selatan and Painan Utara. Data were collected through observation, interviews, validation questionnaires, practicality questionnaires, and pretest-posttest tests. The results showed that the busy book media was highly valid, with scores of 96.64% from material experts, 91.17% from language experts, and 92.04% from media experts. Practicality results were 94.41% from teachers and 87.25% from students, categorized as very practical. The N-gain score was 0.68, indicating moderate effectiveness. Thus, the busy book is valid, practical, and moderately effective for teaching Pancasila in grade II elementary school.